Skalentypen und Statistik: ein Kommentar zu Velleman & Wilkinson (1993) - Ingo Klein (Friedrich-Alexander-Universität Erlangen-Nürnburg, Lehrstuhl für Statistik und Ökonometrie, 2004)
Velleman & Wilkinson (1993) give a lot of examples to show that the hierarchy of scalers introduced by Stevens is misleading. We will show that these examples gain are misleading if we accept that most real data sets stem come derived measurement. For derived measurement the absolute scale is very important. Count data, ranks, percent data, standardized variables all have an absolute scale.
Keywords: 330; Scale type; permissible transformations; data transformation